Nonrespiratory Sinus Arrhythmia - Barbosa Filho José; Barbosa Paulo Roberto B.; Cordovil Ivan (Arquivos Brasileiros de Cardiologia, 2002)
We report here 2 cases of sinus arrhythmia considered to be a form of nonrespiratory sinus arrhythmia because they did not have variances in the RR interval sequence within the oscillations modulated by respiration. Because the patients had pulsus alternans similar that observed in bigeminy, and because they did not have signs or symptoms of heart failure, we believe the arrhythmias represent intrinsic alterations of the electric activity of the sinus node